1993
DOI: 10.1038/hdy.1993.186
|View full text |Cite
|
Sign up to set email alerts
|

Variation and inheritance of ribosomal DNA in Pinus sylvestris L. (Scots pine)

Abstract: Variability in the ribosomal DNA (rDNA) gene family was surveyed in Scots pine (Pinus sylvestris L.) populations from southern and northern Finland. A total of 97 trees were studied with three restriction enzymes, revealing 13 variable rDNA phenotypes. Each rDNA phenotype represents the combined genotype of the eight rDNA loci (NORs, nucleolus organizer regions) that are present in the Scots pine genome. The studied Scots pine populations were equally variable and there was no evidence of geographic differenti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
4

Year Published

1996
1996
2011
2011

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 38 publications
(35 reference statements)
0
27
0
4
Order By: Relevance
“…PCR-RFLP is more advantageous than Southern blot since it is less time consuming, and also provides the analysis of a higher number of samples simultaneously (Halward et al 1992;Karvonen and Savolainen 1993).…”
Section: Introductionmentioning
confidence: 99%
“…PCR-RFLP is more advantageous than Southern blot since it is less time consuming, and also provides the analysis of a higher number of samples simultaneously (Halward et al 1992;Karvonen and Savolainen 1993).…”
Section: Introductionmentioning
confidence: 99%
“…Ribosomal DNA differentiation was several times higher but still lower than among-population differentiation in bud-set of the same populations. No geographic trends could be revealed for the ribosomal DNA variation (Karvonen and Savolainen 1993). Szmidt et al (1996) reported no RAPD variation between two Swedish Pinus sylvestris populations from latitudes 64° and 67°, respectively.…”
Section: Isozymesmentioning
confidence: 99%
“…This could be the case in L. delicatulum. A similar explanation has been suggested for ITS polymorphism in other plant species (Suh et al, 1993;Karvonen and Savolainen, 1993;Campbell et al, 1997).…”
Section: Intraspecific Variationmentioning
confidence: 78%